O ensino da produção textual: uma sequência didática com o gênero artigo de opinião - Pes, Silvânia de Araujo (2018)
It is not of today that defends the need for change in the approach to reading, writing, and orality activities performed in school space, whereas what is detected is that, even after several years of schooling, the students have difficulties to express themselves orally or in writing efficiently. However, despite academic debates, researches and studies, mostly, the practices of textual production teaching continue to request of the student the writing of artificial and out of context texts, not taking into account that the interaction process is what conducts the text production in the social environment, and, thus, needs to think in alternatives to reduce the artificiality aspect of production in school. In this context, arises as methodological option the work with textual genres, aiming to expand proposals activities with reading and text production. Specifically about the teaching of textual production, is defended a work that consider the conditions of production and circulation of texts. In view of this reality, this research has as general objective to investigate teaching strategies aimed to production of genre opinion article in the classroom. For this purpose, first, proceeded to a literature review that approached the textual production in an enunciative perspective, considering the text as a form of interaction between people. In a second moment, it was developed a working practical proposal with the students, guided by theoretical propositions addressed. The production proposal of opinion article was applied to a class of 1º year of High School, composed by 24 students, at the Rui Barbosa State Institute, in São Luiz Gonzaga municipality. The activity was developed in the form of a didactic sequence, as proposed by Schneuwly and Dolz (2010). In this job, report the development of activities performed and the obtained results. The theoretical bases which based the reflections made in this study are, mainly, Bakhtin (2011), Marcuschi (2008), Serafini (1997) and Ruiz (2015).